A brain-computer interface implantable medical connector and its preparation method

By employing vacuum brazing technology between a multi-channel alumina ceramic substrate and a pure titanium ring frame, the airtightness and signal crosstalk issues of existing implantable connectors have been resolved, achieving stability and biocompatibility in high-density EEG signal transmission and improving the overall performance of the connector.

CN122075748APending Publication Date: 2026-05-26HEFEI SHENGDA ELECTRONIC TECH IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610080920.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-21
Publication Date
2026-05-26

AI Technical Summary

Technical Problem

Existing implantable connectors suffer from insufficient airtightness, signal crosstalk, poor biocompatibility, and a limited number of channels, making it difficult to meet the needs of high-density EEG signal transmission.

Method used

Employing a multi-channel alumina ceramic substrate, a pure titanium ring frame, and pure gold solder, a fully circumferential airtight structure is formed by vacuum brazing the side metallization layer with the pure gold solder. Combined with tungsten paste-filled channels and a precise annular groove design, insulation resistance and biocompatibility are ensured.

Benefits of technology

It achieves high airtightness, insulation and biocompatibility, with a leakage rate of less than 1×10-10 Pa·m³/s and an insulation resistance of ≥1×10¹² Ω, supporting high-density EEG signal transmission and reducing the risk of signal crosstalk and inflammatory response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122075748A_ABST
    Figure CN122075748A_ABST
Patent Text Reader

Abstract

This invention discloses a brain-computer interface implantable medical connector and its fabrication method, belonging to the field of biomedical engineering. The connector comprises a multi-channel alumina ceramic substrate, a pure titanium ring frame, and pure gold solder. The sides of the ceramic substrate are fully coated with a tungsten metallization layer and electroplated with nickel-gold. An annular groove is formed in the inner ring of the pure titanium ring frame to accommodate the solder. The ceramic substrate with multiple tungsten paste-filled through-holes is fabricated using the HTCC process. Vacuum brazing is then used to weld the sides of the ceramic substrate to the titanium ring frame, forming a fully circumferentially airtight structure. This invention uses all medical-grade materials, exhibiting excellent biocompatibility. The unique side metallization and ring frame groove design significantly improves welding reliability and airtightness, with a leakage rate ≤1×10⁻⁶. ‑10 Pa·m 3 / s; High-purity alumina ceramic and the isolation channel design ensure high insulation, with an insulation resistance ≥1×10⁻⁶ between adjacent channels. 12 Ω. This invention solves the technical problems of insufficient airtightness, easy signal crosstalk, and poor biocompatibility of existing implantable connectors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of brain-computer interface biomedical engineering, specifically to a brain-computer interface implantable medical connector and its preparation method. Background Technology

[0002] Brain-computer interfaces (BCIs) are a core technology for connecting the brain to external devices. Their implantable connectors must meet stringent requirements such as biocompatibility, high airtightness, high insulation resistance, multi-channel transmission, and structural stability. After being implanted in the human body, they must withstand long-term corrosion from bodily fluids, avoid signal crosstalk, and achieve high-density EEG signal transmission through tiny dimensions.

[0003] Existing implantable connectors have the following technical defects: 1) The ceramic-metal welding interface is prone to porosity and peeling, resulting in insufficient airtightness (leakage rate higher than 1×10). -8 (Pa•m³ / s), causing device failure after bodily fluid intrusion; 2) Inadequate insulation structure in multi-channel designs, with insulation resistance below 1×10⁻⁶ Pa•m³ / s. 10 Ω, which is prone to signal crosstalk; 3) The biocompatibility of the solder or metal substrate is not up to standard, and long-term implantation may cause inflammatory reactions; 4) The number of channels is limited (usually ≤32 channels), which cannot meet the needs of high-density EEG signal acquisition; 5) The welding process is prone to ceramic cracking or metal deformation, affecting structural stability.

[0004] Therefore, developing an implantable medical connector that combines multi-channel high density, high airtightness, high insulation, and biocompatibility is a key breakthrough for the clinical translation of brain-computer interface technology. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects of the prior art and provide a brain-computer interface implantable medical connector and its preparation method. It aims to solve the technical problems of poor air tightness caused by the weak ceramic-metal welding interface, signal crosstalk caused by insufficient insulation between multiple channels, and the difficulty in balancing biocompatibility and long-term reliability of existing implantable connectors, so as to meet the stringent requirements of high-density brain-computer interfaces for long-term stable implantation.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A brain-computer interface implantable medical connector includes a multi-channel alumina ceramic substrate, a pure titanium ring frame, and pure gold solder. The sides of the multi-channel alumina ceramic substrate are fully covered with a metallization layer. An annular groove is formed in the inner circle of the pure titanium ring frame. The pure gold solder is placed in the annular groove. The multi-channel alumina ceramic substrate is welded to the pure titanium ring frame through the metallization layer on its sides via the pure gold solder to form a fully circumferentially airtight structure.

[0008] Preferably, the multi-channel alumina ceramic substrate is made of 99.6% alumina white porcelain and has a racetrack-shaped shape. Multiple uniformly distributed through holes are opened inside the substrate, and the through holes are filled with tungsten paste with a filling density of ≥98%.

[0009] Preferably, the metallization layer is a tungsten metallization layer, with a nickel layer and a gold layer electroplated sequentially on its outer side; the thickness of the nickel layer is 5 μm, and the thickness of the gold layer is 0.5 μm.

[0010] Preferably, the pure titanium ring frame is made of medical-grade TA2G pure titanium, and its shape is a racetrack shape adapted to the multi-channel alumina ceramic substrate; the annular groove has a width of 0.5 mm and a depth of 0.3 mm.

[0011] Preferably, the purity of the pure gold solder is ≥99.99%.

[0012] Preferably, the leakage rate of the airtight structure is ≤1×10⁻⁶. -10 Pa·m 3 / s, and the insulation resistance between any two adjacent through holes corresponding to signal channels is ≥1×10 12 Ω.

[0013] The above-mentioned method for preparing the implantable brain-computer interface medical connector includes the following steps: S1: Preparation of a multichannel alumina ceramic matrix with a side metallization layer; S2: Electroplating nickel and gold layers is performed on the side metallization layer of the ceramic substrate; S3: Pretreatment of the pure titanium ring frame; S4: Place the pre-formed pure gold solder into the annular groove of the pretreated pure titanium ring frame, and assemble and position the electroplated ceramic substrate with the pure titanium ring frame, followed by vacuum brazing to form an airtight structure.

[0014] Preferably, the steps for preparing the ceramic substrate include: preparing a ceramic green body with through holes and filling it with tungsten paste; printing tungsten metallization patterns on the side of the green body; after lamination, isostatic pressing, and debinding, sintering at a high temperature of 1550°C in a humid hydrogen atmosphere; and mechanically leveling and electroless nickel plating on the side of the substrate to be welded after sintering.

[0015] Preferably, the nickel plating layer is plated with nickel sulfamate solution at a current density of 1-1.5 A / dm² to a thickness of 5 μm; the gold plating layer is plated with acidic potassium gold cyanide solution at a current density of 0.3-0.5 A / dm² to a thickness of 0.5 μm.

[0016] Preferably, the nickel plating layer is plated with nickel sulfamate solution at a current density of 1.2 A / dm² to a thickness of 5 μm; the gold plating layer is plated with acidic potassium gold cyanide solution at a current density of 0.4 A / dm² to a thickness of 0.5 μm.

[0017] Preferably, the vacuum brazing is performed under a vacuum of ≤5×10-3 Pa, with the temperature increased to 1085℃ at 10℃ / min and held for 20 minutes, and then cooled to below 200℃ at 10℃ / min.

[0018] Compared with the prior art, the beneficial technical effects of this invention are reflected in: 1. Excellent biocompatibility: TA2G pure titanium, 99.6% alumina white porcelain and pure gold solder have all passed ISO 10993 biocompatibility certification, are non-cytotoxic and can be implanted in the human body for a long time.

[0019] 2. Strong airtightness and structural stability: The sides are fully covered with a tungsten metallization layer to improve the solder wetting effect, the ring frame slots achieve precise solder distribution, vacuum brazing avoids oxidation pores, the leakage rate is ≤1×10-10 Pa•m³ / s, and it effectively prevents body fluid intrusion.

[0020] 3. Outstanding insulation performance: The alumina ceramic itself has high insulation resistance, the 80 tungsten paste-filled channels are mutually isolated, and the electroplated nickel-gold layer further optimizes the insulation effect. The insulation resistance of adjacent channels is ≥1×10¹² Ω, eliminating signal crosstalk.

[0021] 4. High-density transmission adaptation: The design with 80 through holes meets the high-density EEG signal transmission requirements of brain-computer interfaces, and the racetrack-shaped structure adapts to the space constraints of the implantation site, with obvious miniaturization advantages. Attached Figure Description

[0022] Figure 1 Schematic diagram of a multi-channel ceramic medical connector; Figure 2 This is a schematic diagram of the cross-sectional structure of the connector.

[0023] Among them: 100-HTCC multi-channel alumina white ceramic substrate, 200-pure titanium ring frame, 300-pure gold solder, 101-through hole, 102-metallization layer, 201-annular groove. Detailed Implementation

[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0025] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0026] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0027] Please refer to the appendix. Figure 1 and Figure 2 The present invention will now describe an implantable medical connector for a brain-computer interface. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention.

[0028] Example 1: A brain-computer interface implantable medical connector A brain-computer interface implantable medical connector, such as Figure 1 and Figure 2 As shown, its main structure includes: an HTCC multi-channel alumina white ceramic substrate 100, a pure titanium ring frame 200, and pure gold solder 300. The HTCC multi-channel alumina white ceramic substrate 100 is brazed at high temperature under vacuum conditions through the metallization layer 102 on its side and the pure gold solder 300 placed in the annular groove 201 of the pure titanium ring frame 200, thereby achieving full circumferential and hermetic welding between the ceramic substrate and the titanium ring frame, forming a complete hermetic packaging structure.

[0029] (1) HTCC Multichannel Alumina White Porcelain Substrate 100: The material is 99.6% high-purity alumina ceramic powder, manufactured by HTCC (High Temperature Co-fired Ceramic) process. The substrate has a racetrack-shaped shape with a major axis of 19.8 mm, a minor axis of 10.8 mm, and a thickness of 0.7 mm, to adapt to the skull or tissue space of a specific implantation site. 80 uniformly distributed through holes 101 are opened inside the substrate, with a diameter of 0.25 mm and a center-to-center distance of 0.5 mm. These through holes 101 constitute signal transmission channels. Each through hole 101 is filled with tungsten paste and compacted. To ensure the quality of the filling, the filled green ceramic piece is placed under a light source and inspected with a 10x microscope to check for any incomplete or missing filling. The filling material inside the hole is visually dense and uniform. The channel does not participate in welding, but only serves as a signal transmission isolation structure. After the tungsten paste is filled, the channel and the ceramic substrate are sintered together to form a conductive path and firmly bonded to the ceramic body. The side surface of the alumina white ceramic substrate 100 (i.e., the surface in contact with the pure titanium ring frame 200) is fully covered with a tungsten metallization layer 102, with a thickness of 20-25 μm. This tungsten metallization layer 102 is formed by screen printing tungsten paste and co-firing it with the ceramic substrate. On the outer side of the tungsten metallization layer 102, a nickel layer with a thickness of 5 μm and a gold layer with a thickness of 0.5 μm are electroplated in sequence to improve the conductivity, oxidation resistance, and solder wettability of the welding interface.

[0030] (2) Pure titanium ring frame 200: The material is medical-grade TA2G pure titanium conforming to GB / T 13810-2017 standard, which has good biocompatibility. The ring frame is racetrack shaped to match the shape of the ceramic substrate. At the contact position between the inner ring of the ring frame and the metallized layer 102 on the side of the alumina white ceramic substrate 100, an annular groove 201 is precisely machined. The groove is 0.5mm wide (matching the width of the solder preform) and 0.3mm deep (approximately 1.5 times the thickness of the solder, reserving space for the flow and filling of the solder after melting). This annular groove 201 is used to accurately place the pure gold solder 300 to ensure that the solder is evenly distributed during the brazing process.

[0031] (3) Pure gold solder 300: Pure gold foil or wire with a purity ≥ 99.99% is used. Its biocompatibility meets the ISO 10993 standard, is suitable for the welding characteristics of ceramics and titanium metals, and avoids corrosion from body fluids. The solder is pre-processed into a ring shape that matches the size of the annular groove 201 and placed in the annular groove 201. The volume of the solder is calculated to ensure that after melting, it can fully fill the gap between the ceramic metallization layer and the titanium ring frame and form a full weld bead, while avoiding excessive solder overflow that contaminates the channel area.

[0032] (4) Airtight structure The sides of the alumina white ceramic substrate 100 are vacuum brazed to a pure titanium ring frame 200 using pure gold solder 300 to form a fully circumferential hermetically sealed package. After welding, the solder forms a metallurgical bond with the metallized layer on the ceramic side and the titanium ring frame, resulting in a continuous and dense interface free of visible cracks, pores, or other defects.

[0033] Example 2 A method for preparing a brain-computer interface implantable medical connector as described in Embodiment 1 includes the following steps: S1: Preparation of HTCC multichannel alumina white ceramic substrate. This step specifically includes: S11. A ceramic green body is prepared using 99.6% alumina powder, and 80 through holes with a diameter of 0.25 mm are drilled on the green body using laser drilling.

[0034] S12. Use an extrusion filling process to fill the through holes with tungsten paste, with a filling density ≥98%, and scrape the surface to ensure compaction.

[0035] S13. Circuit patterns are printed on the surface of the ceramic green body using screen printing technology and then leveled by hot pressing.

[0036] S14. Align the multi-layer printed ceramic green bodies by stacking (alignment accuracy ±0.01mm), and compact them by isostatic pressing. The typical pressure range is 100-300Mpa, the holding time is 2-30 minutes, and the depressurization rate is 10-50Mpa / min.

[0037] S15. A tungsten metallization layer is printed on the side of the laminated blank (i.e., the subsequent welding surface) using screen printing.

[0038] S16. Perform adhesive removal treatment: Heat to 500℃ at a heating rate of 5℃ / min, hold for 3 hours, and remove organic adhesive.

[0039] S17. High-temperature sintering: Sinter at 1550℃ for 4 hours in a humid hydrogen atmosphere with a hydrogen ratio of 3%-5% H2 / N2 and a dew point temperature range of +25℃ to +35℃, followed by furnace cooling.

[0040] S18. Mechanically level the sintered ceramic matrix.

[0041] S19. The leveled ceramic substrate is subjected to electroless nickel plating. The electroless nickel plating solution mainly consists of 20-30 g / L nickel sulfate, 20-30 g / L sodium hypophosphite, 20-30 g / L lactic acid (complexing agent), 10-15 g / L sodium acetate (buffer), 1-2 mg / L potassium iodate (stabilizer), and trace amounts of wetting agent and pH adjuster. The process conditions are: temperature 85-92℃, pH range 4.5-5.2, and plating time 30 minutes. After plating, a uniform and dense nickel-phosphorus alloy layer is formed on the substrate surface. This serves as the underlayer for electroplating, preparing for subsequent welding with metals or continuity testing.

[0042] S2: Ceramic substrate electroplating treatment.

[0043] Electroplating is performed on a ceramic substrate that has undergone electroless nickel plating: S21. Electroplated nickel layer: To improve the density and adhesion of the plating layer, it is preferred to use a nickel sulfamate plating solution (nickel sulfamate concentration range 300-450g / L) and electroplate to a nickel layer thickness of 5μm at a current density of 1.2A / dm².

[0044] S22. Electroplating of gold layer: Using an acidic potassium gold cyanide plating solution (gold concentration 1-2 g / L), electroplating is performed at a current density of 0.4 A / dm² until the gold layer thickness is 0.5 μm.

[0045] S3: Pre-treatment of pure titanium ring frame.

[0046] The machined TA2G pure titanium ring frame is cleaned. S31. Place in degreasing solution and perform ultrasonic cleaning at 60°C for 1 hour.

[0047] S32. Gently scrub the surface with a nylon brush, then rinse three times with running deionized water.

[0048] S33. Place in a vacuum drying oven and dry at 100℃ for 1.5 hours.

[0049] S4: Assembly and Vacuum Brazing S41. Using a dedicated high-precision, high-purity graphite substrate and a high-purity yttrium oxide ceramic positioning mold, the electroplated ceramic substrate, the pure titanium ring frame, and the pre-formed ring-shaped pure gold solder are assembled and positioned in sequence to ensure that the solder is located in the ring groove; the assembly is then placed in a vacuum brazing furnace.

[0050] The key design considerations for the positioning mold are: 1. Good biocompatibility and chemical inertness. Y₂O₃ is one of the oxides with low reactivity with titanium and gold, and does not form compounds with titanium and gold, thus maintaining the purity of the brazing environment to a large extent. 2. Excellent titanium vapor barrier properties. The surface is dense, and after titanium vapor condenses on its surface, it is easy to remove during subsequent cleaning because it does not wet or react.

[0051] S42. Start the brazing procedure: a. Evacuate the furnace until the internal pressure is ≤ 5×10⁻⁶. - ³ Pa; b. Increase the temperature to 1085℃ at a rate of 10℃ / min.

[0052] c. Hold at 1085℃ for 20 minutes to allow the solder to fully melt, wet, and form a metallurgical bond.

[0053] d. After the heat preservation is completed, the furnace is cooled to below 200°C at a rate of 10°C / min. Then the heating is turned off and the furnace is allowed to cool naturally to room temperature under vacuum or inert gas protection to prevent oxidation and thermal stress cracking.

[0054] Example 3: Performance Testing and Comparative Analysis To objectively evaluate the core performance of the brain-computer interface implantable medical connector prepared by this invention, its airtightness and insulation resistance were tested in accordance with relevant national standards.

[0055] Test methods and conditions 3.1 Air tightness test: According to method 1014.2 of GJB548B-2005, the air tightness of five connector samples (numbered A1-A5) was tested using a UL 1000 helium mass spectrometer. The samples were placed under 0.5 MPa helium gas for 5 minutes, and the leakage rate was measured. Acceptance criterion: ≤1×10⁻⁶ -10 Pa·m³ / s. The test results are shown in Table 1.

[0056] 3.2 Insulation Resistance Test: Following GJB548B-2005 Method 3021, a high-resistance meter (model 4339B) was used to test the insulation performance between adjacent signal channels inside the connector of sample A1. The test method was as follows: a voltage of 500 V was applied to any two adjacent signal channels, and the resistance value was read after stabilizing for 60 seconds. The insulation resistance between adjacent channels should be ≥1×10⁻⁶. 12 Ω indicates a passing grade. The test results are shown in Table 2.

[0057] Table 1 Connector airtightness test record

[0058] Table 2 Insulation resistance test record

[0059] The airtightness test results showed that the leakage rate measurements of all tested samples met and exceeded the preset acceptance criteria. Specifically, the leakage rate of samples A1 to A5 remained stable at 10%. -11 The Pa·m³ / s order of magnitude demonstrates that the side metallization and slotted vacuum brazing structure employed in this invention can form an extremely dense and reliable encapsulation interface. This is significantly lower than the leakage rate, typically higher than 1×10⁻⁶, caused by welding defects in existing technologies mentioned in the background section. -8 To address the technical problem of Pa·m³ / s, this invention improves the airtightness of the connector by at least two orders of magnitude, thereby effectively preventing the intrusion of biological fluids such as body fluids and tissue fluids. This provides a key guarantee for the long-term stable operation of implantable devices in the complex biochemical environment in the body and significantly reduces the risk of system failure due to encapsulation failure.

[0060] Insulation resistance test results show that, under the 80-channel high-density integrated structure, the insulation resistance value between adjacent channels of the connector of the present invention is consistently 4.7 × 10⁻⁶. 12 Ω to 6.1×10 12 The insulation resistance is between Ω, far exceeding the acceptable standard. This verifies the superior performance of the insulation system constructed from a high-purity alumina ceramic matrix, tungsten paste-filled isolation channels, and precisely localized side metallization layers. This is in contrast to the existing connectors mentioned in the background section, where the insulation resistance is generally below 1×10⁻⁶ due to poor insulation structure. 10 Overcoming the limitations of Ω, the insulation performance of this invention is improved by more than two orders of magnitude. This characteristic ensures that signal crosstalk between channels is suppressed to an extremely low level during high-density, microvolt-level EEG signal transmission, thereby significantly improving the signal-to-noise ratio and fidelity of signal acquisition and meeting the core requirements of modern high-precision brain-computer interfaces for signal transmission quality.

[0061] Based on the above test data on airtightness and insulation resistance, the brain-computer interface implantable medical connector provided by this invention achieves a synergistic enhancement effect through its unique material system and structural design, successfully breaking through the technical bottleneck of the prior art where airtightness and insulation are difficult to balance.

[0062] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

[0063] It should be particularly noted that the various embodiments listed in this specification and accompanying drawings are intended to illustrate the technical solutions and advantages of the present invention, and not to limit the scope of protection of the present invention. Without departing from the core ideas and technical effects of the present invention, those skilled in the art can make any form of improvement, substitution, combination, or modification to the structural arrangement, process parameters, material selection, control logic, etc., of the described embodiments; any obvious changes based on the same concept should be considered equivalent solutions of the present invention and should be included within the scope of protection defined by the claims of the present invention. The actual scope of protection of the present invention is determined by the appended claims and should be correctly understood in conjunction with the specification and accompanying drawings.

Claims

1. A brain-computer interface implantable medical connector, characterized in that, Includes a multi-channel alumina ceramic substrate, a pure titanium ring frame, and pure gold solder; The sides of the multi-channel alumina ceramic substrate are fully covered with a metallization layer. The inner ring of the pure titanium ring frame has an annular groove. The pure gold solder is placed inside the annular groove; The multi-channel alumina ceramic substrate is welded to the pure titanium ring frame via a side metallization layer to form a fully circumferential airtight structure using pure gold solder.

2. The brain-computer interface implantable medical connector according to claim 1, characterized in that: The multi-channel alumina ceramic substrate is made of 99.6% alumina white porcelain and has a racetrack-shaped shape. Multiple uniformly distributed through holes are opened inside the substrate, and the through holes are filled with tungsten paste with a filling density of ≥98%.

3. The brain-computer interface implantable medical connector according to claim 1, characterized in that: The metallization layer is a tungsten metallization layer, with a nickel layer and a gold layer electroplated sequentially on the outer side; the thickness of the nickel layer is 5 μm, and the thickness of the gold layer is 0.5 μm.

4. The brain-computer interface implantable medical connector according to claim 1, characterized in that, The pure titanium ring frame is made of medical-grade TA2G pure titanium, and its shape is a racetrack shape adapted to the multi-channel alumina ceramic substrate; the annular groove has a width of 0.5 mm and a depth of 0.3 mm.

5. The brain-computer interface implantable medical connector according to claim 1, characterized in that: The purity of the pure gold solder is ≥99.99%.

6. The brain-computer interface implantable medical connector according to claim 1 or 2, characterized in that, The leakage rate of the airtight structure is ≤1×10 -10 Pa·m 3 / s, and the insulation resistance between any two adjacent through holes corresponding to signal channels is ≥1×10 12 Ω.

7. A method for preparing a brain-computer interface implantable medical connector according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1: Preparation of a multichannel alumina ceramic matrix with a side metallization layer; S2: Electroplating nickel and gold layers is performed on the side metallization layer of the ceramic substrate; S3: Pretreatment of the pure titanium ring frame; S4: Place the pre-formed pure gold solder into the annular groove of the pretreated pure titanium ring frame, and assemble and position the electroplated ceramic substrate with the pure titanium ring frame, followed by vacuum brazing to form an airtight structure.

8. The preparation method according to claim 7, characterized in that, The steps for preparing the ceramic substrate include: preparing a ceramic green body with through holes and filling it with tungsten paste; printing tungsten metallization patterns on the side of the green body; after lamination, isostatic pressing, and debinding, sintering at a high temperature of 1550℃ in a humid hydrogen atmosphere; and chemically plating nickel on the side of the substrate to be welded after sintering.

9. The preparation method according to claim 7, characterized in that, The nickel plating layer is plated with nickel sulfamate solution at a current density of 1-1.5 A / dm² to a thickness of 5 μm; the gold plating layer is plated with acidic potassium gold cyanide solution at a current density of 0.3-0.5 A / dm² to a thickness of 0.5 μm.

10. The preparation method according to claim 7, characterized in that, The vacuum brazing is performed at a vacuum level ≤ 5 × 10⁻⁶. -3 The process is carried out at Pa, with the temperature increased to 1085℃ at 10℃ / min and held for 20 minutes, and then cooled to below 200℃ at 10℃ / min.